2006
DOI: 10.1007/s00027-006-0831-8
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls, mercury, and potential endocrine disruption in fish from the Hudson River, New York, USA

Abstract: Tissue residues of total mercury (Hg), total polychlorinated biphenyls (PCBs), and lipid-based PCBs; plasma concentrations of endocrine biomarkers; and reproductive and histologic biomarkers were assessed in 460 carp (Cyprinus carpio), bass (Micropterus salmoides and Micropterus dolomieui), and bullhead (Ameiurus nebulosus) collected from eight sites across the Hudson River Basin in the spring of 1998 to determine if endocrine disruption was evident in resident fish species and to evaluate contaminant-biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 44 publications
6
38
2
Order By: Relevance
“…Other contaminants may have varied among individuals as we found that our ''clean'' females in 2011 contained low concentrations of DDE (i.e., many contaminants covary; Baldigo et al 2006). Most studies focus on contaminants in target tissues that influence endocrine function such as liver, gonad, and brain, whereas we quantified total body burden.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other contaminants may have varied among individuals as we found that our ''clean'' females in 2011 contained low concentrations of DDE (i.e., many contaminants covary; Baldigo et al 2006). Most studies focus on contaminants in target tissues that influence endocrine function such as liver, gonad, and brain, whereas we quantified total body burden.…”
Section: Discussionmentioning
confidence: 94%
“…Large body size is related to increased reproductive output in males within many species, because big males may be selected by females, are often superior competitors for mates, and may produce more sperm (Wedell et al 2006). Poor growth, exposure to disease, selective harvest (Parkos et al 2011), and contaminants (Baldigo et al 2006) may reduce male reproductive output. Persistent organic pollutants, such as polychlorinated biphenyls (PCBs), may interfere with male reproduction due to their potential to bioaccumulate and disrupt endocrine processes associated with reproduction (Derocher et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…EROD activity may be suppressed by the presence of estradiol or its synthetic homologues of suppression (Arukwe and Goksøyr 1997;Solé et al 2000). The same substances, on the other hand, seem to induce vitellogenin in the male fish liver (Baldigo et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of total wet-weight PCBs in fish increased to 40-100 g/g (3% lipid) in 1992 and these concentrations persisted for a few years before decreasing after 1994 (Sloan et al, 2005). Since the 1970s, fish inhabiting the Hudson River have been extensively sampled to record PCB concentrations in fish (Sloan et al, 1984;Fabrizio et al, 1991;Butcher et al, 1997;Sloan et al, 2005;Baldigo et al, 2006). In a review of published papers, Monosson (1999) speculated that PCBs concentrations in fish inhabiting the upper Hudson River in the early to mid-1990s were high enough to cause reproductive endocrine disruption and affect subsequent reproduction, survival, and growth of young fish.…”
Section: Introductionmentioning
confidence: 97%
“…In a review of published papers, Monosson (1999) speculated that PCBs concentrations in fish inhabiting the upper Hudson River in the early to mid-1990s were high enough to cause reproductive endocrine disruption and affect subsequent reproduction, survival, and growth of young fish. In addition, using data collected in 1998, Baldigo et al (2006) hypothesized that PCBs, mercury, or other contaminants may have been related to alterations in endocrine biomarkers which affect reproduction of black bass including largemouth bass (Micropterus salmoides) and smallmouth bass (M. dolomieu) in the upper Hudson River. However, Maceina and Sammons (2013) found no relation between reproductive success measured by electrofishing catch rates of age-1 fish and total wet-weight PCBs of 1-3 g/g in muscle tissue of adult wild largemouth bass, smallmouth bass, and yellow perch (Perca flavescens) from 2003 to 2009 in the same areas sampled in the upper Hudson River by Baldigo et al (2006).…”
Section: Introductionmentioning
confidence: 99%